Subarachnoid haemorrhage (spontaneous aneurysmal) - Javadpour, Mohsen (BMJ Publishing Group, 2009)
INTRODUCTION: Subarachnoid haemorrhage (SAH) may arise spontaneously or as a result of trauma. Spontaneous SAH accounts for about 5% of all strokes. Ruptured aneurysms are the cause of 85% of spontaneous SAH. The most characteristic clinical feature is sudden-onset severe headache. Other features include vomiting, photophobia, and focal neurological deficit or seizures, or both. As the headache may have insidious onset in some cases, or may even be absent, a high degree of suspicion is required to diagnose SAH with less typical presentations. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of surgical treatments for people with confirmed aneurysmal subarachnoid haemorrhage? What are the effects of medical treatments to prevent delayed cerebral ischaemia in people with confirmed aneurysmal subarachnoid haemorrhage? We searched: Medline, Embase, The Cochrane Library, and other important databases up to March 2009 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 6 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: endovascular coiling; surgical clipping; timing of surgery; and oral and intravenous nimodipine.